Increasing Fuel Cell Efficiency by Using Ultra-Low Equivalent Weight Ionomers. (1st January 2017) - Yandrasits, Michael; Lindell, Matthew; Schaberg, Mark; Kurkowski, Michael
Abstract : Proton exchange membranes based on perfluorosulfonic acid (PFSA) ionomers are the industry standard for proton exchange membrane fuel cells. These ionomers offer remarkable proton conductivity and chemical stability, especially when fully hydrated with water. Performance, however, rapidly decreases as the membranes dry out, thereby requiring external humidification equipment. Because of this, there exists a need for new ionomers that can maintain high proton conductivity at low humidification levels. Perfluoro bissulfonimides have acid strengths similar to those of sulfonic acids and can be used to extend the polymer side chain with an additional protogenic group. These polymers have been designated PerfluoroSulfonImide Acid (PFIA) or PerfluoroIonene Chain Extended (PFICE) ionomers. Compared to PFSAs, these ionomers have improved conductivities under all humidity conditions, however, the benefit of these improvements are most significant under the driest conditions.